Midtarsal locking, the windlass mechanism, and running strike pattern: A kinematic and kinetic assessment. (17th May 2018) - Bruening, Dustin A.; Pohl, Michael B.; Takahashi, Kota Z.; Barrios, Joaquin A.
Abstract: Changes in running strike pattern affect ankle and knee mechanics, but little is known about the influence of strike pattern on the joints distal to the ankle. The purpose of this study was to explore the effects of forefoot strike (FFS) and rearfoot strike (RFS) running patterns on foot kinematics and kinetics, from the perspectives of the midtarsal locking theory and the windlass mechanism. Per the midtarsal locking theory, we hypothesized that the ankle would be more inverted in early stance when using a FFS, resulting in decreased midtarsal joint excursions and increased dynamic stiffness. Associated with a more engaged windlass mechanism, we hypothesized that a FFS would elicit increased metatarsophalangeal joint excursions and negative work in late stance. Eighteen healthy female runners ran overground with both FFS and RFS patterns. Instrumented motion capture and a validated multi-segment foot model were used to analyze midtarsal and metatarsophalangeal joint kinematics and kinetics. During early stance in FFS the ankle was more inverted, with concurrently decreased midtarsal eversion (p < 0.001) and abduction excursions (p = 0.003) but increased dorsiflexion excursion (p = 0.005). Dynamic midtarsal stiffness did not differ (p = 0.761). During late stance in FFS, metatarsophalangeal extension was increased (p = 0.009), with concurrently increased negative work (p < 0.001). In addition, there was simultaneously increased midtarsal positive work (p < 0.001), suggesting enhanced power transfer in FFS. Clear evidence for the presence of midtarsal locking was not observed in either strike pattern during running. However, the windlass mechanism appeared to be engaged to a greater extent during FFS.